2017
DOI: 10.1139/cjpp-2016-0374
|View full text |Cite
|
Sign up to set email alerts
|

Gastroprotective effects of montelukast andNigella sativaoil against corticosteroid-induced gastric damage: they are much more than antiasthmatic drugs

Abstract: Corticosteroids are used to treat a variety of diseases like bronchial asthma. However, long-term corticosteroids have a gastric ulcerogenic potential. Montelukast (MTK) and Nigella sativa oil (NSO) are used in treatment of bronchial asthma. Previous studies showed that MTK and NSO had gastroprotective effects in other models of gastric ulcer. The present study assesses synergistic gastroprotective effects of both drugs in dexamethasone (DXM)-induced gastric damage. Fifty male rats were divided into 5 groups: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 36 publications
0
1
1
Order By: Relevance
“…They also proposed that montelukast has an anti-inflammatory action as demonstrated by significant decrease in MPO activity of gastric tissue caused by dexamethasone treatment as well as by the improved histopathological picture of the stomach in the form of decreased edema and mononuclear cells. In contrast to the present work where histopathological examination of the stomach showed loss of mucin, the authors reported that montelukast treatment caused increased mucus production in the stomach by unknown mechanisms [22] .…”
Section: Discussioncontrasting
confidence: 99%
“…They also proposed that montelukast has an anti-inflammatory action as demonstrated by significant decrease in MPO activity of gastric tissue caused by dexamethasone treatment as well as by the improved histopathological picture of the stomach in the form of decreased edema and mononuclear cells. In contrast to the present work where histopathological examination of the stomach showed loss of mucin, the authors reported that montelukast treatment caused increased mucus production in the stomach by unknown mechanisms [22] .…”
Section: Discussioncontrasting
confidence: 99%
“…Nigella sativa (N. Sativa) annual herb of the Ranunculaceae family, also known as the Black seed with a great historical and religious background, is mostly cultivated in Southwest Asia, southern Eu-rope, and North Africa [7]. Studies have reported that black seed contains a bioactive component called thymo quinone (TQ) that have numerous benefits like immunomodulatory, anti-inflammatory [8], hepato protective [9], diuretic [10], antihypertensive [11], hypoglycemic [12], hypo lipid emic [13], anti-microbial [14], and gastro protective [15] effects; thus it is used to treat various diseases like cancers, diabetes, and neurodegenerative diseases [5]. Cannabis or hemp seed is originated from China and has been mostly used to produce textile and animal food.…”
Section: Introductionmentioning
confidence: 99%